2010
DOI: 10.1159/000320387
|View full text |Cite
|
Sign up to set email alerts
|

High-Salt Diet and Hypertension: Focus on the Renin-Angiotensin System

Abstract: A high-salt diet is one of the major risk factors in the development and maintenance of hypertension. Numerous experimental and observational studies have confirmed the association of sodium intake with blood pressure levels. The effects of a high-salt diet are related to the function of the renin-angiotensin system, which is normally suppressed by a high-salt diet. Endothelial dysfunction probably plays an important role in the influence of high sodium intake on blood pressure, although the exact mechanisms r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
144
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(157 citation statements)
references
References 199 publications
5
144
1
7
Order By: Relevance
“…The RAS is a predominant homeostatic system that controls body fluid volume, electrolyte balance, blood pressure, and neuronal and endocrine functions associated with cardiovascular control (19). The RAS exerts its effects via its primary effector molecule, Ang II, which binds to specific membrane-bound Ang receptors that are located in various tissues (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RAS is a predominant homeostatic system that controls body fluid volume, electrolyte balance, blood pressure, and neuronal and endocrine functions associated with cardiovascular control (19). The RAS exerts its effects via its primary effector molecule, Ang II, which binds to specific membrane-bound Ang receptors that are located in various tissues (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The RAS exerts its effects via its primary effector molecule, Ang II, which binds to specific membrane-bound Ang receptors that are located in various tissues (19,20). Recent studies have revealed that Chinese herbs regulate the function of the RAS, the sympathetic vagus nerve and the immune system by inhibiting the levels of inflammatory factors (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Certain humans, however, exhibit heightened sensitivity to salt, including a significant proportion (ϳ30%) of persons with essential hypertension (an elevation of blood pressure of unknown origin) (67). In addition to an impaired capacity of the kidney to excrete the added salt, other factors implicated in promoting essential hypertension include a salt-mediated increase in sympathoadrenal activity (41, 65), stimulation of the renin angiotensin system (RAS) (13,20), and impairment of vascular endothelial function (7).Typically, experimental studies of essential hypertension utilize animal models derived from genetically modified inbred strains of rodent (12) or exploit increased dietary salt supplements in animals experiencing compromised renal function (e.g., via unilateral nephrectomy). However, in freshwater (FW) rainbow trout (Oncorhynchus mykiss), dietary salt loading [e.g., (59)] is capable of inducing chronic hypertension in fish experiencing otherwise normal kidney function (10, 14, 39).…”
mentioning
confidence: 99%
“…Certain humans, however, exhibit heightened sensitivity to salt, including a significant proportion (ϳ30%) of persons with essential hypertension (an elevation of blood pressure of unknown origin) (67). In addition to an impaired capacity of the kidney to excrete the added salt, other factors implicated in promoting essential hypertension include a salt-mediated increase in sympathoadrenal activity (41, 65), stimulation of the renin angiotensin system (RAS) (13,20), and impairment of vascular endothelial function (7).…”
mentioning
confidence: 99%
“…Skorije studije na eksperimentalnim životinjama ukazale su na ključni značaj mutacija renin gena i drugih gena odgovornih za kodiranje RAS (renin-anitotenzin sistem) u so zavisnim hipertenzijama (91 Jedan od vodećih zaključaka do kojih su došli istraživači okupljeni oko INTERSALT studije je da uporedo sa starenjem, dolazi do porasta vrednosti krvnog pritiska, ali samo u populacijama sa visokim unosom soli (2). Tada je uočen izuzetak iz ovog pravila među pripadnicima amazonskog plemena Janomano indijanaca kod kojih nije došlo do porasta vrednosti krvnog pritiska sa starenjem, ali je unos soli bio svega oko 1 gram dnevno (2,94).…”
Section: Hipertenzija I Unos Soliunclassified